Damage to temporary canopy structure by wind load - Muhammad Arifin, Ramli (2014)
Numbers of incidents regarding the failure of the temporary structure were widely reported due to the windstorm in Malaysia. The incidents cause injuries and fatalities to people. The canopy structure is one of the temporary structures that widely used in Malaysian surroundings during the small occasion ceremony. Due to the lack of information, mitigation of this kind of hazard is tough to be mitigated. The most important parameter is the potential wind speed that can cause the failure to the canopy. Previous study conducted this structures can be classified as free standing canopy structures. However there are no specific studies conducted for common canopy used in Malaysia. Two common type of canopy structure were identified and analysis due to wind load. Type A is 3m x 3m and Type B is 6m x 6m. The canopy was imposed with two different major direction of wind load. From the result type A canopy will possibility fail at 11 m/s while type B at 13 m/s. Therefore this result information can be use to mitigate the risk of failure on canopy structures due to wind load.